DEVELOPMENT OF FLIPBOOK TEACHING MATERIALS BASED ON CULTURE FUSION SEDATI TO IMPROVE CLASS V STUDENTS' SCIENCE LEARNING OUTCOMES SD NEGERI 45 BANDA ACEH - Ainal Mardhiah; Lili Kasmini; Siti Mayang Sari (Pena Cendekia Insani, 2026)
This study aims to develop flipbook teaching materials based on Sedati culture fusion in the subject of science to improve the learning outcomes of fifth-grade students at SD Negeri 45 Banda Aceh. This research was conducted in Banda Aceh City as part of the study in the Master of Elementary Education Program at Bina Bangsa Getsempena University. The type of research used is Research and Development (R&D) with the ADDIE development model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The subjects of the study were fifth-grade students with the material